Estimating electromagnetic velocity in Ground Penetrating radar by Normal MoveOut (NMO) - Vấn, Nguyễn Thành; Triết, Võ Minh; Trung, Đặng Hoài; Cường, Lê Văn Anh; Giảng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2014)
Ground penetrating radar (GPR) is a high-resolution near-surface geophysical method which employs radio waves, typically in the 10 to 2000 MHz frequency range to map structure and features buried in the ground (or in man-made structures). Electromagnetic (EM) velocity is an essential parameter in GPR. There are many solutions to determine EM velocity for geological medium. The characteristics of groundwave on CMP radagram for EM velocity are the best ways, but most of modern GPR systems could not easily separate transmitter and receiver antennae. Normal MoveOut (NMO) which is frequently used in seismic prospecting is a good resolution for estimating velocity. Studying variations of wave field in the NMO method give us an overall view about the distribution of radar velocities, which are useful for precise interpretation the depths and sizes of objects in survey areas. This study shows some results that were done by a program from Matlab in alculating GPR velocities of some computational models and practical data by the NMO method.